The influence of digital entrepreneurial skills, digital literacy and entrepreneurship education on digital entrepreneurship outcomes among youth - Azman, Hartini; Shahrim, Aimi Aqilah; Sufian, Atirah; Mohd Jamel, Nur Erma Suryani (Research and Scientific Innovation Society, 2026)
Digital entrepreneurship has become increasingly important in Malaysia’s digital economy, yet many young individuals lack the capabilities required to achieve sustainable digital business outcomes. This study examines the influence of digital entrepreneurial skills, digital literacy, and entrepreneurship education on digital entrepreneurship outcomes among youth in Pahang, Malaysia. The objective of the study is to determine the relationships between these factors and to identify the most influential predictor of digital entrepreneurship outcomes. A quantitative, cross‑sectional research design was employed. Data were collected using a structured online questionnaire distributed to 411 youths aged 18–34 years in Kuantan and Temerloh, Pahang, selected through purposive sampling. The data were analysed using Statistical Package for Social Sciences (SPSS), applying descriptive statistics, reliability analysis (Cronbach’s Alpha), Pearson correlation, and multiple regression analysis. The results indicate that digital entrepreneurial skills, digital literacy, and entrepreneurship education all have a positive and significant relationship with digital entrepreneurship outcomes (p < 0.001). Among the predictors, digital literacy emerged as the strongest determinant, followed by digital entrepreneurial skills and entrepreneurship education. The regression model explained 86.3% of the variance in digital entrepreneurship outcomes. The study concludes that strengthening youth digital literacy, alongside practical entrepreneurial skills and education, is essential for improving digital entrepreneurship outcomes. These findings offer valuable implications for policymakers, educators, and entrepreneurship development programmes aimed at supporting youth participation in the digital economy.